Correlates of sleep pattern among college students in Chandigarh - Kaur, Manjot; Walia, Dinesh K.; Sharma, Manoj K. (International Journal Of Community Medicine And Public Health, 2023)
Background: Adequate sleep is an essential element for maintaining good health. Sleep disturbances in the general community particularly among university students are an essential health problem to be addressed. "Sleep disturbance" is defined by the sleep foundation as an interruption of sleep that results in arousal or awakening. The goal of this study was to ascertain the prevalence of sleep disruptions and the factors related to sleep. Methods: This was a cross-sectional study, conducted among 256 college-going students. A self-administered questionnaire was used to collect data, which was pre-tested and pre-designed. Descriptive and analytical statistics were utilized, with analytical statistics being conducted using the Chi-square test and binomial logistic regression to find the risk factors associated with sleep disturbances. Results: Out of 256 students, 161 (62.9%) were suffering from sleep disturbances. A majority of participants preferred to sleep after 10 pm. The mean hours of sleep received by 256 participants were 6.67 hours. A strong significant association was found between sleep disturbances and any stress in life affecting sleep, sleep quality after COVID-19, worried about test and exams, smoking, have a bed partner or roommate, Illness during past month and papers, assignments and research papers due. Conclusions: The present study reported a high prevalence of students having sleep disturbance irrespective of their socio-demographic characteristics. Sleep disturbance was increased having to worries due to exams, any illness or having stress of any kind in their lives. The study suggests some measures should be taken to create quality sleep-friendly environment for students reducing academic stress and encouraging healthy life style.